2015
DOI: 10.1159/000371464
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Features of Reproductive Hormone Profiles in Late Adolescent and Adult Females with Complete Androgen Insensitivity Syndrome

Abstract: Little is known about gonadotropins and sex steroid levels in postpubertal women with complete androgen insensitivity syndrome (CAIS). In order to define reproductive hormone profiles in women with CAIS and intact gonads, 42 postpubertal females with proven CAIS (age range 14-50 years) with testes in situ were examined. Reproductive hormone values [testosterone (T), estradiol (E2), sex hormone-binding globulin (SHBG), luteinizing hormone (LH), follicle-stimulating hormone (FSH)] were assessed by commercially a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 32 publications
0
49
1
2
Order By: Relevance
“…A histological report (year 1961) described a dysgenetic-like testis structure with seminiferous tubules containing only Sertoli cells, but slides were not available for a re-examination; remnants of müllerian structures were also found (immature Fallopian tubes but not uterus). When she was 18 years old, she was diagnosed with complete androgen insensitivity syndrome because of primary amenorrhea and 46,XY karyotype, but clinical findings (absence of breast development, normal pubic and axillary hair) and endocrine data (LH, 105 IU/L; FSH, 210 IU/L; both testosterone and 17β-estradiol undetectable) were not consistent with such a diagnosis [21, 22]. At the age of 20 years, this woman underwent surgery for acute appendicitis and the right gonad was removed.…”
Section: Resultsmentioning
confidence: 99%
“…A histological report (year 1961) described a dysgenetic-like testis structure with seminiferous tubules containing only Sertoli cells, but slides were not available for a re-examination; remnants of müllerian structures were also found (immature Fallopian tubes but not uterus). When she was 18 years old, she was diagnosed with complete androgen insensitivity syndrome because of primary amenorrhea and 46,XY karyotype, but clinical findings (absence of breast development, normal pubic and axillary hair) and endocrine data (LH, 105 IU/L; FSH, 210 IU/L; both testosterone and 17β-estradiol undetectable) were not consistent with such a diagnosis [21, 22]. At the age of 20 years, this woman underwent surgery for acute appendicitis and the right gonad was removed.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have examined the very specific endocrine profiles of women with CAIS [Doehnert et al, 2015]. A conclusion towards "irregular" or "abnormal" cannot be made in this condition as the usual male/female pattern is lacking and therefore a reference population does not exist.…”
Section: The Dilemma Of Gonadectomymentioning
confidence: 99%
“…The underlying condition is a peripheral resistance towards all androgenic steroids due to a mutation of the androgen receptor. This leads to a very specific endocrine environment with slightly elevated LH levels and FSH, testosterone, and estradiol values in the male reference range despite pubertal feminization [Doehnert et al, 2015].The current debate on the prophylactic gonadectomy versus the saving of the testes is inflamed by several points. As reviewed by Cools et al [this issue], an increased risk for testicular germ cell tumors (GCT) has been demonstrated.…”
mentioning
confidence: 99%
“…A typical hormone profile for CAIS patients has the following features: low LH/FSH and elevated testosterone levels at birth, low LH/FSH and low testosterone levels at minipuberty, low LH/FSH and low testosterone levels during infancy and childhood, and elevated LH, normal or mild elevated FSH, and elevated testosterone levels together with an elevated estradiol levels for male reference range after the onset of puberty [11,31,32]. A recent publication reported that basal testosterone and estradiol levels in postpubertal women with CAIS were found in the usual adult male reference ranges [33]. It is necessary to understand the disease-specific hormone profile at each developmental stage for accurate diagnosis.…”
Section: Discussionmentioning
confidence: 99%